Nutritional status and pulmonary outcome in children and young people with cystic fibrosis. (September 2018) - Papalexopoulou, Niovi; Dassios, Theodore G.; Lunt, Alan; Bartlett, Fiona; Perrin, Felicity; Bossley, Cara J.; Wyatt, Hilary A.; Greenough, Anne
Abstract: Background: Nutrition is closely related to mortality and pulmonary and respiratory muscle function in cystic fibrosis (CF) patients. We initially validated results from a bioelectrical impedance device against dual energy x-ray absorptiometry (DEXA). We then determined whether fat free mass assessed by a portable impedance device rather than body mass index (BMI) better correlated with pulmonary function, respiratory muscle strength and exercise capacity in CF patients. Methods: Eighteen young people and adults (median age 19, range 12–39 years) with CF had dual energy X-ray absorptiometry and direct segmental multi-frequency impedance analysis. Body composition, pulmonary function, respiratory muscle function and exercise tolerance using the impedance device were measured in 29 young people with CF with median age 15 (range 12–19) years. Main findings: There was a significant correlation between impedance and absorptiometry results (r 2  = 0.947). Fat free mass correlated with the forced vital capacity z-score (r = 0.442, p = 0.016), maximal inspiratory pressure (r = 0.451, p = 0.014) and exercise tolerance (r = 0. 707, p < 0.001). BMI z-scores did not significantly correlate with pulmonary or respiratory muscle function. Subjects with a fat free mass z-score of ≤2 had a lower forced expiratory volume in 1 s z-score (p = 0.007), lower forced vital capacity z-score (p = 0.001), higher residual volume z-score (p = 0.042), lower maximal inspiratory pressure (p = 0.039), more days of intravenous antibiotics per year (p = 0.016) and a higher rate of chronic infections (p = 0.006). Principal conclusions: Fat-free mass measured by impedance correlated better with pulmonary and respiratory muscle function and exercise capacity than BMI. Highlights: We validated a bioelectrical impedance device by dual energy x-ray absorptiometry. In CF patients there was a high correlation between impedance and DEXA. Free fat mass assessed by impedance correlated with pulmonary function results. Body mass index did not significantly correlate with pulmonary function results.